Base filosófica da liberdade política anglo-saxônica e da liberdade política francesa e sua presença no constitucionalismo norte- americano - Wright, Anthony Tannus (2013)
This work aimed to discuss the philosophical basis of the Anglo-Saxon political liberty and the French Political liberty present in the North-American Constitutionalism. The first part of this research dealt with the historical, religious and political changes that culminated in a substantial mentality change of a theocentric medieval society to an anthropocentric society, founder of the modern state. Hence, the objective of this first part was to show the historical roots of the English and French liberal thought. Before discussing the central theme a political and philosophical comparison between the English, French and American Revolution was done. With this purpose the writings of Locke, Montesquieu, Rousseau, Blackstone, and of other liberal theorists served as reference. Furthermore, to better comprehend the difference of English and French liberalism an investigation of what the terms government, political liberty, state and republic, etc., seemed necessary. A historical and political study of the common law tradition and of natural rights served to better elucidate the basis of the American Constitution. To end, a research on the Founding Fathers and on the Federalist Papers was key point to comprehend how one should read and interpret the Constitution in light with English classical liberalism